ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PERPINDAHAN MEREK MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi pada bekas konsumen pembersih wajah Pond’s di kota Semarang) - Putro, Ismail Wahyudi; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2014)
This research is motivated by the phenomenon of brand switching behavior on brand Pond's facial cleanser. With the decline in brand image in the product, it can be one of the triggers a decline in customer satisfaction impact on brand switching behavior in the pond's facial cleanser products to other brands. The purpose of this study was to determine the effect of brand image, quality products to the brand switching behavior through consumer satisfaction as an intervening variable in the consumer Pond's facial cleanser in Semarang. The population in this study is that consumers ever use Pond's facial cleanser and have switched to another brand of other facial cleaning products that are domiciled in the city of Semarang. The sample in this study was 100 respondents using purposive sampling method. The analytical tool used is multiple linear regression analysis were first tested with validity and reliability. From the analysis using regression can be seen that brand image variable (X1), product quality (X2) jointly influence on consumer satisfaction (Y1) with the results of linear analysis, is Y1= 0,420X1+0,389X2. With the brand image is the most influential variable positively to customer satisfaction followed by the quality of the product. Both of these variables influence of 34.6% on customer satisfaction while the remaining 65.4% can be influenced by other variables. As well as consumer satisfaction variable (Y1) negatively affect the migration behavior of consumers (Y2) with the results of linear analysis is Y2= -0,406Y1. This variable affects 15.6% of the brand switching behavior while the remaining 84.4% can be influenced by other variables.